Brand Image, Service Quality and Promotion on Alfamart Customer Satisfaction in Sidoarjo (Citra Merek, Kualitas Pelayanan dan Promosi Terhadap Kepuasan Pelanggan Alfamart di Sidoarjo) - Hariasih, Misti; Tinanto, Bagus Tegar; Indayani, Lilik (Indonesian Journal Publisher, 2024)
The purpose of this study was to determine brand image, service quality and promotion on Alfamart customer satisfaction in Sidoarjo. By using a quantitative approach, this approach can be used to test the theory objectively by looking at the relationship between variables. Sampling was taken using the Non Probability Sampling technique with the purposive sampling method, the total sample being 100 Alfamart customers in Sidoarjo. Data analysis technique uses Least Square (PLS) using SmartPLS version 3.0 software. The results of the study include: Brand Image has a significant effect on Customer Satisfaction. Service Quality has a significant effect on Customer Satisfaction. Promotion has a significant effect on customer satisfaction.